Integrasi Nilai-Nilai Dharma Agama dan Dharma Negara Dalam Tradisi Upacara Hindu di Bali - Hartaka, I Made (Jurnal Penelitian Agama Hindu, 2025)
The application of religious dharma in Bali is evident in religious rituals and also in the implementation of public policies that prioritize local cultural values. If we look at it, dharma in Hinduism is a good action based on Hindu teachings performed by Hindus for the development and interests of Hinduism. This aligns with the dharma of the state, which serves as a guideline regulating societal activities, including religious activities, to ensure they comply with regulations set by the state, such as regional regulations and public order. The purpose of this research is to analyze the intersection or connection between religious dharma and state dharma in the context of traditions or ceremonies in Bali. This research uses a qualitative method with a phenomenological approach. The results of this study are the dharma of religion and the dharma of the state in Hinduism, the manifestation of the values of the dharma of religion and the dharma of the state in religious ceremonies, the potential for conflict and resolution in the implementation of the dharma of religion and the dharma of the state, and the implications of integrating the values of the dharma of religion and the dharma of the state. The conclusion of this research shows that the integration of religious dharma and state dharma not only preserves the continuity of Balinese Hindu traditions but also strengthens the role of indigenous communities within the framework of the Indonesian rule of law. This integration can be strengthened through the development of regulations.